Processos oxidativos avançados no tratamento de água contaminada pelo herbicida atrazina - Lourenço, Edneia Santos de Oliveira (2014)
Agriculture in general has become dependent on pesticides. Among the classes of pesticides, herbicides followed by insecticides and fungicides are the most marketed. The Atrazine (ATZ) is a selective herbicide recommended for weed control due to its high potential for leaching has been detected frequently in natural waters.The aim of this study was to evaluate the efficiency of processes: Fenton,solar and artificial photo-Fenton, solar and artificial photolysis and H2O2/UV in the treatment of water contaminated with atrazine and its toxicity using Lactuca sativa L. species. The experiments were conducted in laboratory scale. The reactor consisted of a beaker with borosilicate in batch system. The survey was conducted in three stages. In the first step an experimental design was proposed: central rotational compost design (CRCD) by artificial photo-Fenton process having five levels as a variable concentration of ATZ (5,86; 10; 20; 30 and 34,14 mgL-1) and five levels of Fe2+(15,14; 40; 100; 160; 184,85mgL-1). The operating parameters of the reactors were based on statistically significant response reduction of dissolved organic carbon (DOC). Subsequently the best conditions were reproduced assessing the mineralization of atrazine in Fenton, artificial photo-Fenton, artificial photolysis and H2O2 /UV processes. In the second stage was performed the same planning through the Fenton process using five levels of iron (1,76; 3; 6; 9 e10,24 mgL-1) and five levels of hydrogen peroxide (15,86; 20; 30; 50 and 58,28 mg L-1). The best conditions obtained in the planning were reproduced in the kinetic tests in Fenton process, artificial photo-Fenton, solar photo-Fenton and solar photolysis taking in response to ATZ degradation and mineralization processes. In the third step it was performed the toxicity test of treated ATZ using Lactuca sativa L. seeds in response to the germination and hypocotyl elongation. The results showed that the efficiency of Fenton is improved by the presence of artificial and solar lights and increasing process efficiency. After 120 min of reaction ATZ reduced by 98%, while the FFA and FFS in only 40 min of reaction reduced to 90% under the same conditions. Solar photolysis was the less efficient: in 120 min reaction only reduced the concentration of ATZ by 40%. The process was more efficient in reducing and mineralization of ATZ was the photo-Fenton artificial, but during the degradation process is likely to have formed intermediates, which showed high toxicity in relation to germination, radicle growth and elongation hypocotyls. The greatest inhibition occurred at concentrations of 30% and ATZ treated without dilution (100%). Despite the significant reduction of ATZ, it did not reach the maximum permissible values (VMP) of 2μg L-1 established by OMS (2004) and CONAMA (2011). Advanced oxidation processes seed in this research showed that they are efficient reducing the concentration of ATZ to considerable values and it could be an alternative for the pesticide packaging recycling companies, since it uses clean and renewable energy, and reagents of easy access. However to improve the toxic conditions to the living organisms and the environment, it is suggested a complementary treatment